Luminescent Properties of Europium Complex Enhanced by Replacement of Water Molecules by 2,2’-Bipyridine - Kumar, Rajesh; Arora, Rajni; Boora, Priti; Taxak, V.B.; Khatkar*, S.P. (Asian Journal of Chemistry, 2014)
The complex [Eu(L)3(bipy)] (where L = 2'-hydroxy-4'-methoxyacetophenone, bipy = 2,2'-bipyridine) was synthesized and characterized by elemental analysis, energy dispersive X-ray spectroscopy, 1H NMR spectroscopy, infra red spectroscopy, TGA/DTA, scanning electron microscopy and the excitation as well as emission spectrum. The [Eu(L)3(bipy)] had regular shaped particles with size less than 1 μm without any phase separations and on excitation at 384 nm emits bright red luminescent with main peak at 612 nm. The complex emitting red luminescent might be used to make the electroluminescent (EL) devices.